A study on sustainability practices in the Malaysian Hospitality Industry - Kaur, Jasvinder (2014)
The hospitality industry encompasses an extensive variety of services that include food service, tourism and hotels. It can be considered a major service sector in the world economy today and described as an industry that has a great impact on the environment, discharging a huge amount of raw and solid waste, constituting a threat to the environment. While much as been done to promote tourism in Malaysia through activities such as Visit Malaysia Year (VMY), very little is done to ensure a sustainable development of the hospitality industry in Malaysia and the preservation of the natural environment for future generations. Of late, there is a growing concern on hotel organisations, as a sector of the tourism industry whose activities afflict the environment to start looking into its environmental impact. Therefore it is important that the hospitality sector in Malaysia consider more proactive measures in implementing sustainability practices in order to remain competitive globally or fail to compete with those designed as such. Some of the findings in this study have further clarified drivers and barriers that effect sustainable practices in the hospitality industry in Malaysia. It is hoped that findings from this research will add value to the existing body of knowledge and inspire policy makers and industry regulators to take the appropriate measures to ensure a sustainable growth of the hospitality industry and for the generations by supporting increased investment on implementing sustainable practices to conserve, preserve and protect the natural environment.